2016
DOI: 10.1111/resp.12818
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use and asthma outcomes among patients with concurrent asthma and diabetes

Abstract: Background and objective: Metformin is a first-line treatment for patients with diabetes. Recent animal studies indicated that metformin can reduce airway inflammation. However, it remains unclear whether the use of metformin can help patients maintain asthma control. The purpose of this study was to evaluate the association between the use of metformin and asthmarelated outcomes, which include asthma-related hospitalization, asthma-related emergency room visits and asthma exacerbation, among patients with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 42 publications
2
66
0
Order By: Relevance
“…Provocative studies have shown the potential of metformin, DPP-4 inhibitors, and statins in treating asthma (Huang et al, 2011; Li et al, 2016; Nader, 2015; Zeki et al, 2013). And while the GLP-1 pathway may also be effective, it is unclear which phenotypes of asthma it may help.…”
Section: Resultsmentioning
confidence: 99%
“…Provocative studies have shown the potential of metformin, DPP-4 inhibitors, and statins in treating asthma (Huang et al, 2011; Li et al, 2016; Nader, 2015; Zeki et al, 2013). And while the GLP-1 pathway may also be effective, it is unclear which phenotypes of asthma it may help.…”
Section: Resultsmentioning
confidence: 99%
“…Exactly how insulin resistance might promote asthma in the obese has not been established, but there is evidence of effects of insulin both on the immune system and on airway smooth muscle (71, 72). A retrospective analysis of data from 1332 patients with asthma and diabetes indicated lower risk of asthma hospitalization in patients who were taking metformin for treatment of their diabetes than in those who were not (73). However, a randomized controlled trial of treatment with another type 2 diabetes therapeutic, pioglitazone, indicated little benefit in obese asthmatics.…”
Section: Obesity Increases the Severity Of Asthmamentioning
confidence: 99%
“…A recent retrospective study in adults found that the use of metformin among patients with diabetes and asthma was associated with improved asthma outcomes 102 . Metformin, which acts via AMP-protein kinase (AMPK), has been shown to decrease eosinophilic airway inflammation and inhibit airway smooth muscle hypertrophy in murine models 103,104 .…”
Section: Weight Loss and Management Of Obesity Complicationsmentioning
confidence: 99%